From Admission To Recovery: The Integrated Roles Of Medical Secretaries, Social Workers, And Nursing Staff In Shaping The Cardiovascular Thoracic Surgery Care Pathway (The Review of Diabetic Studies, 2025)
Background: Cardiovascular thoracic surgery (CVTS) requires a highly coordinated, multidisciplinary approach to ensure optimal patient outcomes. While surgical techniques are well established, the combined roles of nursing staff, psychosocial professionals, and administrative coordination in shaping the CVTS care pathway remain insufficiently synthesized in the literature.Methods: An integrative review methodology was applied following Whittemore and Knafl guidelines. A systematic search of PubMed, Scopus, Web of Science, and ScienceDirect identified studies published between 2020 and 2025. Eight peer-reviewed studies met inclusion criteria and were analyzed according to nursing contributions, psychosocial support, interprofessional collaboration, and workflow elements relevant to cardiac and thoracic surgery.Results: Nursing staff demonstrated the strongest direct influence on postoperative safety and recovery, with evidence showing improved outcomes in settings with higher nurse-to-patient ratios and specialty-trained cardiovascular or thoracic nurses (Driscoll et al., 2017; Messina et al., 2024; Audet et al., 2024). Psychosocial interventions—including emotional assessment, counseling, and family engagement—significantly enhanced psychological stability and rehabilitation adherence (Savio et al., 2020; Callus et al., 2020). Interprofessional collaboration improved communication, continuity of care, and patient trajectories, especially when advanced practice nurses and psychosocial professionals were fully integrated. Evidence regarding administrative coordination was limited, highlighting an important gap for future research.Conclusion: CVTS outcomes depend on the integrated actions of specialized nursing, structured psychosocial support, and effective interprofessional collaboration. Developing comprehensive care models that incorporate these domains can improve safety, efficiency, and patient-centered recovery across the CVTS continuum.